The Effect of Rewards on Innovative Behaviour or Creativity based on Literatures regarding Experimental Study and The Implication of Relevant Arrangement - Rolando, Mohammad Rizqi; Sirajulhuda, Mohammad Hanief (RJABM (Research Journal of Accounting and Business Management), 2025)
This article explores whether providing rewards (intrinsic or extrinsic) may improve employees’ creativity or even adversely affect creativity, which finally affects company performance. By raising this topic, the writers would like to offer an alternative view compared to the common perception from those who are assuming that financial rewards can be so powerful to encourage employees to strive for excellence, while ignoring intrinsic rewards that may be beneficial to increase employees’ motivation and engagement. This review is supported by literatures, an experimental study and a relevant case on a specific topic; the effect of rewards on innovative behaviour or creativity. It has been demonstrated that rewards and creativity tend to have no simply link and even lessen employee’s creativity if positive variable support is not considered.